2005
DOI: 10.1590/s1516-44462005000200012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eating disorders and psychiatric comorbidity in a clinical sample of type 2 diabetes mellitus patients

Abstract: In our study sample, the occurrence of eating disorders was increased compared to rates observed in the general population, with the predominance of binge eating disorder. The presence of an eating disorder in type 2 diabetes mellitus patients was associated with higher rates of anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…Evaluation of psychiatric conditions has shown that the presence of DEBs and eating disorders are associated with comorbid anxiety disorders (Papelbaum et al, 2005) and elevated levels of depressive symptoms (Herpertz et al, 2001) in T1D patients and depressive symptoms and obesity in T2D patients (Nicolau et al, 2015; Çelik et al, 2015; Hood et al, 2014). …”
Section: Disordered Eating Behaviors and Eating Disordersmentioning
confidence: 99%
“…Evaluation of psychiatric conditions has shown that the presence of DEBs and eating disorders are associated with comorbid anxiety disorders (Papelbaum et al, 2005) and elevated levels of depressive symptoms (Herpertz et al, 2001) in T1D patients and depressive symptoms and obesity in T2D patients (Nicolau et al, 2015; Çelik et al, 2015; Hood et al, 2014). …”
Section: Disordered Eating Behaviors and Eating Disordersmentioning
confidence: 99%
“…5,9 An association of ED with T1D may be much more hazardous than an ED alone in that it involves a serious lack of metabolic control, higher mortality rates and higher risk of complications, such as diabetic retinopathy. 10,11 Studies on this subject in Brazil have focused on the presence of BED in T2D 12 and have also included reviews 13,14 and case studies. 15 Due to the importance and complexity of both ED and T1D, as well as the lack of research on Brazilian samples of patients with T1D and ED, the objective of this study was to evaluate the presence of risk behaviors for ED in adolescents and adults with T1D and to investigate possible associations of these behaviors with gender, nutritional status, variables related to T1D, and body satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Papelbaum et al reported that occurence of eating disorders increased in type 2 diabetes mellitus patients compared to rates observed in the general population, with the predominance of binge eating disorder. 25 They reported that presence of an eating disorder was associated with higher rates of anxiety disorders. Anxiety has been reported to be as high as 30-40% in persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%